EFFECTIVENESS OF THE SIMMAMAH (READY TO SERVE THE COMMUNITY AT NIGHT) PROGRAM AT THE TAMAN SUB-DISTRICT OFFICE, SIDOARJO - Kuncoro, Javier Firjatullah Nizar; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyse the effectiveness of the SIMMAMAH (Ready to Serve the Community at Night) Program which is an innovation in population administration services in Taman District, Sidoarjo Regency. The background of this programme is to provide services to people who do not have free time during regular working hours. This research uses descriptive qualitative methods with data collection techniques through interviews, direct observation, and documentation. Method: The analysis in this study refers to the theory of effectiveness according to Duncan which includes three main indicators, namely goal achievement, integration, and adaptation. Result: The results show that the SIMMAMAH Programme is effective in reaching out to the community, especially to those who work during the day, as shown by the increasing number of service users for documents such as Family Cards (KK) and Child Identity Cards (KIA) from 2022 to 2023. The programme has also been integrated with the village service system and continues to run despite leadership changes. In terms of adaptation, SIMMAMAH shows flexibility in operational time but still faces constraints on fixed scheduling and limited information dissemination. Novelty: The result of this research lies in the in-depth analysis of non-regular time (night-time) based public service innovations and the importance of schedule flexibility and more effective communication strategies to improve accessibility of civil registration services.